The Negotiation of First Agreements in Ontario: An Empirical Study - Solomon, Norman (Relations industrielles / Industrial Relations, 1984)
The purpose of this study is to analyse bargaining units which achieved first agreements and those that did not achieve first agreements in terms of data relating to their OLRB certification experience and in terms of data relating to basic bargaining unit characteristics.